2020
DOI: 10.1037/sah0000193
|View full text |Cite
|
Sign up to set email alerts
|

Reducing mental-illness stigma via high school clubs: A matched-pair, cluster-randomized trial.

Abstract: We examined the effectiveness of a student-initiated and guidebook-supported high school club program aimed at reducing mental-illness stigma via humanization—largely through contact—hypothesizing that stigma measures would improve across a school year and as a function of the timing of club initiation. Forty-two Northern California high schools (731 students) participated from 2015–2017. Stigma measures (Knowledge, Attitudes, Social Distance, and Positive Actions) were collected in the fall (Time 1 [T1]), win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…One study found mixed results, as significant improvement was observed with one of the vignettes only ( p < .001) but not the other ( p = .056; Hart et al., 2018). Four studies found no significant differences in behavioural intentions towards people with mental disorders (Ahmad et al., 2020; Chisholm et al., 2016; DeLuca et al., 2020; Swartz et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study found mixed results, as significant improvement was observed with one of the vignettes only ( p < .001) but not the other ( p = .056; Hart et al., 2018). Four studies found no significant differences in behavioural intentions towards people with mental disorders (Ahmad et al., 2020; Chisholm et al., 2016; DeLuca et al., 2020; Swartz et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies addressed knowledge and awareness of mental disorders (Ahmad, Leventhal, Nielsen, & Hinshaw, 2020; Aseltine & DeMartino, 2004; Chan, Mak, & Law, 2009; Chisholm et al., 2016; DeLuca, 2020b; DeLuca, Tang, Zoubaa, Dial, & Yanos, 2020; Klingman & Hochdorf, 1993; Link et al., 2020; Milin et al., 2016; Nguyen et al., 2020; Painter et al., 2017; Perry et al., 2014; Pinto‐Foltz, 2009; Pinto‐Foltz et al., 2011; Rahman, Mubbashar, Gater, & Goldberg, 1998; Swartz et al., 2017; Teesson et al., 2020; Yamaguchi et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggestion is also consistent with calls for adolescent stigma reduction programs to consider cognitive and socioemotional features of adolescent development (Newcomb-Anjo, 2019). Other researchers have suggested interactive interventions for youth via active learning strategies, incorporating youth stories, and promoting youth leadership (Ahmad, Leventhal, Nielsen, & Hinshaw, 2020; Austin & Schwartz, 2019; Bulanda, Bruhn, Byro-Johnson, & Zentmyer, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…United Nations (UN) experts have predicted that “from the 21 st century, mental problems will be the chief culprit that plagues people's development and causes many other problems” [ 5 ]. The World Health Organization (WHO) has estimated that six of the top 20 major diseases will be mental diseases by 2020, accounting for 17.4% of all diseases [ 6 ]. As far as the level of mental health teaching in Chinese universities is concerned, some students with mental problems are unable to receive effective mental counseling and treatment in time due to the lack of mental counselors, which in turn leads to more students jumping off buildings and committing suicide [ 7 ].…”
Section: Introductionmentioning
confidence: 99%